ANALISIS PENERAPAN PSAK 24 IMBALAN PASCAKERJA PADA PT. PERKEBUNAN NUSANTARA XI - Ulum, Bustanul (Fakultas Ekonomi Universitas Gresik, 2019)
This study aims to examine and prove the effectiveness of post-employment benefits at PT. Perkebunan Nusantara XI is in accordance with PSAK 24. This research is important because there are still a number of companies that are still blind about the application of PSAK 24, causing employee welfare to be inadequate. This study uses a descriptive qualitative approach by taking some data and conducting interviews with employees regarding the post-employment benefits obtained. The results of this study are PT. Perkebunan Nusantara XI has implemented a post-employment benefit program in accordance with PSAK 24 and provides facilities for employees to participate in a defined and effective contribution programDOIÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â 10.5281/zenodo.3629909